SDN controllers security issues - Imran, Ayesha (2017)
Software-Defined Networking (SDN) is essentially varying the way we design and manage networks, which makes a communication network programmable. In SDN, a logically centralized controller has straight control over the packet-handling functions of the network switches, using a standard, open API (Application Programming Interface) such as OpenFlow. OpenFlow is a broadly used protocol for software-defined networks (SDNs) that presents a new model in which the control plane is inattentive from the forwarding plane for the network devices. In SDN approach centralized entities called "controllers" perform like network operating systems run dissimilar applications that accomplish and control the network via well-defined APIs. SDN permits network engineers and administrators to reply rapidly to the changing business requirements by determining traffic from the central controller deprived of having to touch the physical switches. They use software to rank, redirect or block traffic globally or in varying degrees down to individual packet levels. In short, SDN can deal with the more protected network if it is properly secured. SDN has the ability to transform the network industry. It is observed that currently enterprises requiring SDN deployment demand, multiple controllers that lead security challenges associated with SDN Controller design. In this thesis, a comprehensive literature review concerning SDN controllers security has been done. We demonstrate a comprehensive study on SDN by clarifying its concept, the OpenFlow protocol architecture and how it works, general benefits and applications of SDN. We also present a discussion on SDN controllers and several threat vectors which may enable for the exploitation of the vulnerabilities of SDN Controllers. This study also focuses on designing a dependable Controller platform including the requirements for a secure, resilient, and robust SDN Controller. The thesis is finalized by discussing that how we can secure SDN controllers by making recommendations for security improvements for future SDN Controllers. The discussion highlights the existing gap between the actual security level of the current SDN Controller design and the potential security solutions.